Towards integrated service delivery for children with autism spectrum disorder in the Western Cape Province of South Africa - Pillay, Sarosha (Division of Occupational Therapy, 2024)
Background The prevalence of autism spectrum disorder (ASD) in South Africa is unknown and there is little information on the educational service needs of children with ASD in the country. There are no standardized procedures for identification, diagnosis and management of children with autism. The Western Cape is one of the better resourced provinces in the country in terms of ASD services, yet educational opportunities for these children are limited. The Western Cape was therefore used as a case study to understand the landscape of education systems for children with ASD in South Africa. Objectives The objectives of the study were a) to determine the number and profile of children with ASD both in and out of schools in the Western Cape, b) to examine stakeholder views, perspectives and proposed solutions to meet the educational needs of children with ASD and their families, and c) to generate suggestions to strengthen ASD systems and services. Methods An exploratory mixed-methods approach was used across two phases. In the first phase, quantitative provincial educational data were used to describe the profile of children with ASD in the formal public sector education system as well as those waiting for educational services. The second phase used qualitative focus groups and semistructured individual interviews to examine the perspectives and recommendations of caregivers, service providers and government stakeholders about ASD services. Results A systematic database search for children with ASD in the whole provincial educational system, combined with the provincial ‘waiting list' of those waiting for school placement found very low rates of ASD (